Analisis Perbandingan Upah Borongan Vs Upah Harian Tenaga Kerja Dalam Penyusunan Rab Rumah Sederhana (Studi Kasus : Belopa) - Raznilawati Raznilawati; Anggel Erpa Erong Pakiding (Jurnal Ilmu Teknik Sipil Indonesia, 2026)
The construction sector plays a vital role in infrastructure development and economic growth, where project success is highly influenced by the efficient management of cost, time, and quality. One of the largest and most dynamic cost components in project execution is labor wages. This study aims to analyze the comparison of labor costs and financial efficiency levels between the daily wage system and the piece-rate (wholesale) wage system in formulating the Cost Budget Plan (RAB) for a type 36 simple residential house. The case study was conducted on a housing project in Pammanu Village, North Belopa District, Luwu Regency, South Sulawesi, in 2026. The research method applied was descriptive quantitative with a comparative approach. The Analysis of Work Unit Price (AHSP) was formulated based on the latest official national technical regulations applied in 2026, namely the Circular Letter of the Director General of Construction Development Number 47/SE/Dk/2026 regarding Guidelines for Estimating Construction Project Costs, and adjusted to the 2026 local market prices and labor wage fluctuations in Luwu Regency. The financial data analysis revealed that the total pure labor cost under the daily wage scheme was Rp110,000,000, resulting in a total project RAB (including materials, equipment, and a 10% overhead and profit margin) of Rp412,500,000. Meanwhile, the piece-rate wage scheme required a pure labor cost of Rp125,000,000, leading to a total project RAB of Rp429,000,000. There was a nominal budget discrepancy of Rp16,500,000. Based on the economic efficiency formulation, the implementation of the daily wage system proved to be 3.84% more financially efficient than the piece-rate system. Nevertheless, field observations indicated that the piece-rate wage system offers a non-financial advantage in accelerating the project duration due to high worker productivity motivation. This study concludes that the selection of the wage system must be tailored to the project's main priorities: the daily wage method is optimal for cost efficiency (cost-oriented), whereas the piece-rate method is suitable for schedule acceleration (time-oriented).